Macro and micronutrients content of regular diet meals served at Governmental Jordanian Hospitals - El-Qudah, Jafar M. F. (Progress in Nutrition, 2018)
Backgrounds and Objective: Meals of regular diet were evaluated, in seven hospitals located in three cities in the middle region of Jordan. Methods: The diets were evaluated by calculating their mean content of energy, fiber, macronutrients and some micronutrients, then compared with standards. Results: Our results revealed that energy content was less than 2000 Kcal in all hospitals and fiber content was less than 28 g in most hospitals. Carbohydrate (CHO), protein and fat contribution of the total energy in all hospitals were within the acceptable macronutrients distribution range (AMDR) and ranges between 47.1% and 58.1% for CHO, 14.8% and 22.6% for protein and 21.8% and 32.1% for fat. On average, all hospital meals provided a diet low in the following minerals (ca, K ) and vitamins (A,C, D, E, K) and did not meet the nutritional standards. Regular diet contain excessive levels of sodium which exceeded the AI of 1500 mg of sodium and exceeded the UL of 2300 mg.Based on “Choose My Plate” recommendations, out of seven hospitals, 5 met the recommendations for vegetables, and 4 met the recommendations for grains but only 1,2 and 3 hospitals met the recommendations for protein, dairy and fruits, respectively. Conclusion: On the basis of this study, we conclude that many hospitals do not design regular diets to meet dietary recommendations. Careful menu planning should be emphasized and followed. Menus should be evaluated and updated continuously to reflect the changes of the patients’ preferences and requirement.